1H NMR analysis of perdeutero N-sulfoheparosan C5-epimerization: a direct way to measure the activity of immobilized C5-epimerase. Issue 9 (21st November 2020) - Qiao, Meng; Jiao, Ruoyu; Zhang, Xing; Wu, Zhengzhang; Shen, Baoxing; Li, Bingzhi
Abstract: D-Glucuronyl C5-epimerase (C5-epi), which converts D-glucuronic acid to L-iduronic acid, is a crucial enzyme in the preparation of bioengineered heparin, which provides an alternative way to produce safer heparins. Herein, we provided an efficient way to measure the activity of cyanogen bromide-immobilized C5-epi based on proton nuclear magnetic resonance (NMR) analysis of perdeutero N -sulfoheparosan C5-epimerization. In this method, reactions catalyzed by C5-epi could be monitored by real-time 1 D NMR according to the peak intensity change of H-5 from IdoA and GlcA residues in the 1 H NMR spectrum, which is nondestructive of sample and also serves the kinetic property evaluation of immobilized C5-epi. Graphical Abstract: